2021
DOI: 10.1111/eci.13698
|View full text |Cite
|
Sign up to set email alerts
|

Obesity paradox in patients with chronic total occlusion of coronary artery

Abstract: Obesity increases the risks of hypertension, type 2 diabetes mellitus, dyslipidaemia, coronary heart disease, obstructive sleep apnoea and certain types of cancer. 1 In general population, average life expectancy is decreased by 7 years at age of 40 years due to complications from comorbidities. 2 Body mass index (BMI) is the most frequently

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Many studies have disclosed the obesity paradox in CAD, but most are based on the BMI group. A cohort study found that a higher BMI was linked to a reduced risk of all-cause mortality over 3 years, even after adjusting for age, renal function, history of stroke, coronary artery bypass graft, peripheral arterial disease, heart failure, and CTO revascularization status [ 9 ]. Explanations for the obesity paradox have pointed out confounding factors that can introduce bias, which is linked to the perceived survival advantage of individuals with obesity [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have disclosed the obesity paradox in CAD, but most are based on the BMI group. A cohort study found that a higher BMI was linked to a reduced risk of all-cause mortality over 3 years, even after adjusting for age, renal function, history of stroke, coronary artery bypass graft, peripheral arterial disease, heart failure, and CTO revascularization status [ 9 ]. Explanations for the obesity paradox have pointed out confounding factors that can introduce bias, which is linked to the perceived survival advantage of individuals with obesity [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, obese individuals may develop type II diabetes mellitus due to insulin resistance [ 36 , 37 ], followed later by adverse lipid profiles, eventually leading to CAD or other severe cardiovascular complications [ 38 , 39 ]. However, even though obese individuals are more prone to CAD, there have been reports of better prognosis in patients with high BMI after coronary artery occlusion or acute myocardial infarction [ 40 , 41 ]. Underweight individuals (BMI < 18.5 kg/m 2 ) with acute coronary syndromes exhibited a paradoxically worse prognosis than overweight individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These controversial results about the role of obesity in cardiovascular diseases have supported the obesity paradox [ 27 ]. In a study by Tsai et al, in 1301 patients with coronary artery occlusion, it was reported that patients with a high BMI had better outcome and lower all-cause mortality [ 41 ]. To explain this paradox of worse outcome in patients with lower BMI, some investigators have implicated progression of atherosclerosis of culprit lesions in vessels with small lumen diameters after PCI in these patients, even though other metabolic risk factors were absent [ 42 ].…”
Section: Discussionmentioning
confidence: 99%